BREEDING OF F1 HYBRIDS OF PUMPKIN FOR CANNING INDUSTRY - A. M. Shantasov; C. D. Sokolov; A. V. Rogov (Овощи России, 2016)
As a result of crossing with patty pan squash with male sterility, the new parent lines of Cucurbita реро L., «ANZH» and «ANZ», with the original set of morphological traits («kabakson») based on the gene of male sterility of functional type were developed. The F1 hybrids with economically valuable features were obtained. These hybrids are characterized by small fruits of pickling types, high yield and biochemical content.